Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $(G, +)$ and $(H, \circ)$ be groups, $U$ a subgroup of $H$ and $\varphi: G \rightarrow H$ be a group homomorphism, i.e. $$\forall a, b \in G: \varphi(a+b) = \varphi(a) \circ \varphi(b)$$

Is the pre-image $\varphi^{-1}(U) = \{g \in G: \varphi(g) \in U\}$ also a group?

My try

$e_G \in \varphi^{-1}(U)$, because $\varphi(e_G) = e_H$ and $e_H \in U$.

Let $a, b \in \varphi^{-1}(U)$. Then $\exists x, y \in U: \varphi(a) = x$ and $\varphi(b) = y$. As $U$ is a group, $x \circ y \in U$. As $\varphi$ is a group homomorphism, $\underbrace{\varphi(a)}_x \circ \underbrace{\varphi(b)}_y = \varphi(a + b) \in U \Leftrightarrow (a+b) \in \varphi^{-1}(U)$.

But I still need to show: $\forall x \in \varphi^{-1}(U) \exists x^{-1} \in U: x \cdot x^{-1} = x^{-1} \cdot x = e_G$

How can I show this?

share|cite|improve this question
If $\varphi(x) \in U$, then $\varphi(x^{-1}) = \varphi(x)^{-1} \in U$, since $U$ is a subgroup. – Daniel Fischer Aug 26 '13 at 12:42
@DanielFischer: I know. But this doesn't show that $\varphi^{-1}(U)$ has inverse. You only say that inverse elements in $G$ get mapped to inverse elements $H$. – Martin Thoma Aug 26 '13 at 12:45
@moose If $a\in \varphi^{-1}(U)$, then $\varphi (a)\in U$, thus $\varphi (a)^{-1}=\varphi (a^{-1})\in U$ as $U$ is a group. But this means $a^{-1}\in \varphi^{-1}(U)$ (because its image is in $U$) and $\varphi^{-1}(U)$ has inverses. – walcher Aug 26 '13 at 12:50
And that means $x \in \varphi^{-1}(U) \Rightarrow x^{-1}\in \varphi^{-1}(U)$, so $K = \varphi^{-1}(U)$ is closed under inversion (and multiplication). – Daniel Fischer Aug 26 '13 at 12:50
@GerryMyerson: Ok, so I've posted the answer. But I made it community wiki, because the important ideas came from Daniel Fischer and walcher. – Martin Thoma Aug 26 '13 at 13:09
up vote 7 down vote accepted

Let $a \in \varphi^{-1}(U)$ be any element in the pre-image of $U$. This means that $\varphi(a) \in U$. As $U$ is a group, it has an inverse $(\varphi(a))^{-1} \in U$. But homomorphisms are closed under inversion, so $(\varphi(a))^{-1} = \varphi(a^{-1}) \in U$. This means $a^{-1} \in \varphi^{-1}(U)$.

share|cite|improve this answer

set $H=\phi^{-1}(U)$, then $H$ is a group iff $\forall a,b \in H$ we also have $ab^{-1} \in H$ i.e. $\phi(ab^{-1}) \in U$

suppose, then, that $\phi(a)=u \in U$ and $\phi(b)=v \in U$

since $\phi$ is a group-morphism, $\phi(ab^{-1}) = \phi(a) \phi(b^{-1}) = u \phi(b)^{-1} = uv^{-1} \in U$ as $U$ is a group

share|cite|improve this answer

Why not just use the 1 Step Subgroup Test? Please notify me if my attempt here is defectible?

$\phi^{-1}(U)$ is a subgroup iff $\forall a,b \in \phi^{-1}(U)$, $ab^{-1} \in \phi^{-1}(U)$. By definition of preimage, this means $\phi(ab^{-1}) \in U.$ $\iff \phi(a)\phi(b^{-1}) \in U$.

This last line is true. Here's why. $b \in \phi^{-1}(U) \iff \phi(b) \in U \iff$ Its inverse is in U $ \iff (\phi(b))^{-1} = \phi(b^{-1}) \qquad \in U$. Same logic with $a$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.